2018
DOI: 10.1177/0265407518798051
|View full text |Cite
|
Sign up to set email alerts
|

Relationship commitment of Portuguese lesbian and gay individuals: Examining the role of cohabitation and perceived social support

Abstract: Lesbian and gay (LG) individuals strive to form stable relationships, and most of them are successful in doing so. Because successful relationships have benefits for psychological well-being, it is important to investigate factors that help people in same-sex relationships to achieve stable and committed relationships. The Investment Model (IM) proposes commitment to be predicted by satisfaction, quality of alternatives, and relationship investments. We extend this model by proposing two additional variables—c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…In our sample, those high in commitment did not report engaging in fewer PDA behaviors despite levels of minority stress. Together these results help to extend the Investment Model to the application of same-gender couples, adding to a growing body of needed research (e.g., Lehmiller & Konkel, 2013;Rodrigues et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…In our sample, those high in commitment did not report engaging in fewer PDA behaviors despite levels of minority stress. Together these results help to extend the Investment Model to the application of same-gender couples, adding to a growing body of needed research (e.g., Lehmiller & Konkel, 2013;Rodrigues et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…Although chosen families are important for LGBTQ+ individuals, much of the existing research has focused on social support from families of origin (Reczek, 2020). Less research has focused on support from friends but has identified that support from close friends, including heterosexual friends, is important to the relationship quality and overall well‐being of LGBTQ+ individuals (Blair et al, 2018; Blair & Holmberg, 2008; Dane & MacDonald, 2009; Elizur & Mintzer, 2003; Rodrigues et al, 2019). A smaller portion of the literature has specifically compared support from friends and family.…”
Section: Resultsmentioning
confidence: 99%
“…A smaller portion of the literature has specifically compared support from friends and family. In these instances, particularly in terms of social support for romantic relationships, it is often the support from friends that is more strongly associated with outcomes for those in same‐sex relationships (Blair et al, 2018; Blair & Holmberg, 2008; Holmberg & Blair, 2016; Rodrigues et al, 2019). Notably, those in same‐sex relationships consistently report lower levels of perceived support than their counterparts in mixed‐sex relationships, including support specifically for their romantic relationships and particularly from their family members or parents (e.g., Holmberg & Blair, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, younger sexual minority men might be more comfortable with disclosing their sexual identity to friends with whom they share a sense of belonging. In contrast, sexual minority men may be more comfortable disclosing their sexual identity to family members when they have emotional support from an intimate romantic partner (e.g., Martos et al, 2015;Pistella et al, 2016;Rodrigues, Huic, et al, 2019;.…”
Section: Discussionmentioning
confidence: 99%
“…For example, internalized homonegativity has been associated with identity concealment (Gonçalves et al, 2020), dissatisfaction with sex life (Berg et al, 2015), less quality in romantic relationships (Doyle & Molix, 2015;, and less emotional intimacy with the romantic partner (Šević et al, 2016;Thies et al, 2016). To the extent that romantic partners, friends, and parents are important sources of emotional support to sexual minority people (e.g., Bauermeister et al, 2010;Doty et al, 2010;Friedman & Morgan, 2009;Rodrigues, Huic, et al, 2019;Rothman et al, 2012;Whitton et al, 2018), future research should examine if such sources of support moderate some of our findings and their implications for interpersonal relationships and individual well-being. Future research should also seek to further understand the coming out process by using more detailed measures of coming out (e.g., breadth and depth of disclose in the social network) and the engagement in strategies to conceal one's sexual identity from others, and include other relevant measures to assess prejudice and discrimination (e.g., polymorphous prejudice scale; Lopes et al, 2017).…”
Section: Limitations and Future Researchmentioning
confidence: 99%